Role of Elimination Diet in Atopic Dermatitis: Current Evidence and Understanding - Anupam Das; Saumya Panda (Wolters Kluwer Medknow Publications, 2021)
Atopic dermatitis (AD) is a fairly common dermatosis of childhood. In many cases, parents are concerned that food allergy plays a role in their child's symptoms and they ask whether practicing elimination diets would help in controlling the symptoms. In this review, we try to provide concise answers to the questions raised by the parents, apart from addressing the myths associated with elimination diets in AD and provide scientific evidence in favor of or against the common notions. A comprehensive English-language literature search for the role of elimination diet in AD across multiple databases (PubMed, EMBASE, MEDLINE, and Cochrane) for keywords (alone and in combination) was performed. MeSH as well as non-MeSH terms such as "AD," "diet elimination," "treatment," "prevention," "evidence," "blanket elimination," and "specific exclusion diet" were taken into consideration. There is level I evidence to support specific exclusion diets in preselected and screened patients, but there is insufficient evidence to recommend strict (blanket) elimination diets.